Climate Governance and the Amazonian State Executive: the case of mining company Norsk Hydro in Pará - Carlos Eduardo Siqueira; Edir Veiga (Ambiente & Sociedade)
Abstract The climate regime is one of the governance instruments that seeks climate mitigation. In the Brazilian Amazon, the presence of big businesses contributes to the climate crisis. It is important to question what results this region receives from the tax breaks granted by the Brazilian state to multinational companies. The methodology focuses on a case study. The objective is to analyze the relationship between the Pará State Executive and the mining company Norsk Hydro in order to verify the results of tax incentives in view of the sustainability of development in the face of the axiom that the investment made by Transnational companies drives development from the periphery to the center of capital. It turns out that tax breaks rival the basic principles of climate mitigation, creating obstacles for the climate regime to take effect satisfactorily.